2020
DOI: 10.1038/s41598-020-65464-5
|View full text |Cite
|
Sign up to set email alerts
|

Optical mapping of the pig heart in situ under artificial blood circulation

Abstract: The emergence of optical imaging has revolutionized the investigation of cardiac electrical activity and associated disorders in various cardiac pathologies. The electrical signals of the heart and the propagation pathways are crucial for elucidating the mechanisms of various cardiac pathological conditions, including arrhythmia. The synthesis of near-infrared voltage-sensitive dyes and the voltage sensitivity of the FDA-approved dye Cardiogreen have increased the importance of optical mapping (OM) as a prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 29 publications
1
21
0
1
Order By: Relevance
“…Moreover, the use of uncouplers, such as blebbistatin, may induce side effects on electrophysiological parameters of the heart [ 3 , 9 ]. Our study [ 4 ], in agreement with others [ 10 , 11 , 12 ], revealed no significant effect of blebbistatin on the electrophysiological parameters of pig hearts in situ. However, in terms of clinical application, the lack of detailed information on the toxicity of this uncoupler is still a limiting factor in its usage for eliminating contraction artefacts during OM under artificial blood circulation.…”
Section: Om In Situ Under Physiological and Artificial Blood Circusupporting
confidence: 93%
See 4 more Smart Citations
“…Moreover, the use of uncouplers, such as blebbistatin, may induce side effects on electrophysiological parameters of the heart [ 3 , 9 ]. Our study [ 4 ], in agreement with others [ 10 , 11 , 12 ], revealed no significant effect of blebbistatin on the electrophysiological parameters of pig hearts in situ. However, in terms of clinical application, the lack of detailed information on the toxicity of this uncoupler is still a limiting factor in its usage for eliminating contraction artefacts during OM under artificial blood circulation.…”
Section: Om In Situ Under Physiological and Artificial Blood Circusupporting
confidence: 93%
“…The study by our group presents data obtained by using a custom-made frame (glued to the epicardial surface in a special procedure) that enabled us to record optical signals from a 40 × 40 mm area of the pig heart in situ under physiological blood circulation with applied stimulation (500 ms cycle length) or ventricular fibrillation. However, our data revealed that mechanical motion arrest using a frame partially restricts the field of view and does not fully eliminate motion artefacts [ 4 ]. Thus, OM under physiological blood circulation, for which the heart must function as a pump, is easy to create in principle, but complicated to apply for qualitative registration at high spatiotemporal resolution.…”
Section: Om In Situ Under Physiological and Artificial Blood Circumentioning
confidence: 99%
See 3 more Smart Citations